2012
DOI: 10.2302/kjm.61.23
|View full text |Cite
|
Sign up to set email alerts
|

The Medical Association Activity and Pediatric Care after the Earthquake Disaster in Fukushima

Abstract: On March 11, 2011, a gigantic earthquake struck eastern Japan. Utilities such as electricity, water, gas and telecommunication were interrupted. In Koriyama, the City Hall collapsed and government administration offices had to be moved to a nearby baseball stadium that had been designed to include facilities for use during a pandemic. An operations center was set up in this stadium. As members of the Koriyama Medical Association, we following the disaster protocol and set up our operations center in the Koriya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Also, elderly people may need more preparation time because they are more difficult to evacuate and may react differently to medication (Johnson et al, 2006). Furthermore, after the Japanese earthquake in 2011 that damaged a nuclear power plant in Fukushima, midwives advised pregnant women about radiation effects to relieve their worries about the negative impact upon their unborn child (Kikuchi and Kikuchi, 2012). Responders and medical staff should also educate and train themselves in the (health) effects of CBRN agents and in using protective measures to be able to respond appropriately when disaster strikes.…”
Section: Categorisation Of Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, elderly people may need more preparation time because they are more difficult to evacuate and may react differently to medication (Johnson et al, 2006). Furthermore, after the Japanese earthquake in 2011 that damaged a nuclear power plant in Fukushima, midwives advised pregnant women about radiation effects to relieve their worries about the negative impact upon their unborn child (Kikuchi and Kikuchi, 2012). Responders and medical staff should also educate and train themselves in the (health) effects of CBRN agents and in using protective measures to be able to respond appropriately when disaster strikes.…”
Section: Categorisation Of Findingsmentioning
confidence: 99%
“…Interventions following a CBRN event should be practical and supportive: "The first thing people want is practical support, the second thing is to talk or not or talk with people from their own social network; professionals come low down on the list" (Wessely, 2005). 15 studies addressed the importance of the accessibility of support for the affected community (Dodgen et al, 2011, Hick et al, 2011, Lemyre et al, 2010a, Lemyre et al, 2010b, Oordt, 2006and Ritchie et al, 2004 and specific groups such as children and responders (Benedek et al, 2002, Kikuchi and Kikuchi, 2012, Lemyre et al, 2010a, O'Boyle et al, 2006and Vazquez et al, 2010. Various recommendations to facilitate support are given.…”
Section: Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…There is adequate evidence to confirm the necessity of such therapies in preventing the damages of adverse events after PTSD symptoms are observed in a postcatastrophic period (11). Similar studies applying mental support showed very successful results in decreasing postshock symptoms of PTSD, especially among children (12).…”
Section: Introductionmentioning
confidence: 95%